Existence Results for Strong Mixed Vector Equilibrium Problem for Multivalued Mappings - Adem Kılıçman; Rais Ahmad; Mijanur Rahaman (Abstract and Applied Analysis)
We consider a strong mixed vector equilibrium problem in topological vector spaces. Using generalized Fan-Browder fixed point theorem (Takahashi 1976) and generalized pseudomonotonicity for multivalued mappings, we provide some existence results for strong mixed vector equilibrium problem without using KKM-Fan theorem. The results in this paper generalize, improve, extend, and unify some existence results in the literature. Some special cases are discussed and an example is constructed.